Dose-Dependent Effects of Common Antibiotics Used to Treat Staphylococcus aureus on Biofilm Formation - Ali Majidpour; Sara Fathi Zadeh; Mastaneh Afshar; Mohammad Rahbar; Mina Boustanshenas; Marjan Heidarzadeh; Leila Arbabi; Somayeh Soleymanzadeh Moghadam (Iranian Society of Pathology, 2017)
Background & Objective: Staphylococcus aureus, especially methicillin-resistant S. aureus (MRSA), represent serious nosocomial and community infections. Biofilm formation as an important virulence factor may be affected by sub-inhibitory levels of antibiotics. Few studies examined the effects of all therapeutic antimicrobial agents on clinical S.aureus. The current study aimed at observing the inducing and reducing effects of antibiotics, commonly used to treat staphylococcal infections on the production of staphylococcal biofilm. Methods: Four MRSA (1ATCC and 3 clinical) and 1 methicillin-susceptible Staphylococcus aureus (MSSA) strains with biofilm forming ability, evaluated by the Congo red agar (CRA) plate test, were employed. Biofilm formation was measured by crystal violet microtiter plate assay. Cefazolin, rifampicin, vancomycin, oxacillin, clindamycin, cotrimoxazole, minocycline, linezolid, azithromycin, and clarithromycin were added to wells ranging from 0.06to 128 µg/mL (1× to 1/1024 MIC dependent on the MIC value of each strain). Results: The current study showed that azithromycin and vancomycin had a significant inducing effect on biofilm formation. In contrast, linezolid, cefazolin, and clarithromycin, and in the second place, clindamycin and minocycline could inhibit the level of biofilm production in the sub-minimal inhibitory concentrations. Conclusion: The findings demonstrated that the biofilm formation as an important virulence factor may be affected by the subinhibitory levels of antibiotics.